Calciphylaxis in a Hemodialysis Patient: A Rare and Fatal Complication - Hayat Ullah,; Khan, Muhammad Zoaib; Alam, Ifthikhar; Amanullah,; Gillani, Hira Masood; Ahmad, Naveed; Banaras, Faizan (Indus Journal of Bioscience Research, 2025)
Calciphylaxis, or calcific uremic arteriolopathy, is a rare and life-threatening condition primarily seen in patients with end-stage renal disease (ESRD) undergoing dialysis. It is characterized by vascular calcification, thrombosis of dermal arterioles, and subsequent tissue necrosis. We present a case of a 52-year-old female on maintenance hemodialysis who developed progressive skin lesions, later diagnosed as calciphylaxis. Despite early diagnosis and initiation of treatment, the patient succumbed to sepsis due to secondary wound infection. This case underscores the diagnostic challenges and high mortality associated with calciphylaxis in dialysis patients and highlights the need for early intervention and multidisciplinary management.